2018
DOI: 10.1017/stc.2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Special Worship in the British Empire: From the Seventeenth to the Twentieth Centuries

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…93 In this case, these two perspectives were not mutually exclusive, but co-existed and even strengthened each other. 94 The local significance of prayer days and prayer hours could be found more clearly in another important element of prayer day solidarity: charity. One of the ritual deeds expected by the repentant ritual participants was giving alms.…”
Section: Gifts Of Lovementioning
confidence: 99%
“…93 In this case, these two perspectives were not mutually exclusive, but co-existed and even strengthened each other. 94 The local significance of prayer days and prayer hours could be found more clearly in another important element of prayer day solidarity: charity. One of the ritual deeds expected by the repentant ritual participants was giving alms.…”
Section: Gifts Of Lovementioning
confidence: 99%
“…Elsewhere, fasts and thanksgivings continued to be spontaneous affairs, called in response to unexpected events. Joseph Hardwick has shown that British colonial governments in late 19th‐century Australia and South Africa frequently summoned their cosmopolitan populations to observe days of humiliation and thanksgiving in times of drought: there are even examples of Australian and South African governments appointing days of prayer in the 1920s (Hardwick, , ; Hardwick and Williamson, , p. 277). The survival of these antique forms reveals something about the centrality of environmental crisis in Australia's settler history, as well as the extent to which drought was regarded as an aberration, a natural disaster, not as a characteristic of an Australian climate (Sherratt, , pp.…”
Section: Weather Ritualsmentioning
confidence: 99%
“…The task for researchers is to determine the extent to which climatic shocks did indeed prompt a sense of environmental crisis among settler communities, one that transcended gender, class and ethnic differences. Preliminary research on 19th‐century Australia suggests that we today might not always find useful lessons in these past examples, as ministers often struggled to build a sense of shared responsibility: town dwellers felt they had no reason to observe days of humiliation during droughts, as the visitation had been sent to punish sinful farmers, not innocent townspeople (Hardwick and Williamson, , p. 278). Nevertheless, it is in the sermons delivered in times of drought, and their emphasis on humility, shared communal responsibility and stewardship of nature, that we might find lessons for our climatic crisis.…”
Section: Weather Ritualsmentioning
confidence: 99%